2020
DOI: 10.1002/slct.202000510
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled Planar Chemical Garden in a 3D Solution

Abstract: Addition of calcium chloride solution in sodium phosphate results in the formation of a closed chemobrionic bubble. Subsequent addition of sodium ethylenediaminetetraacetate results in the formation of radially growing fingers that finally yield new types of quasi‐2D chemical gardens that resemble waterlilies and trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5] For the past four centuries, numerous studies of these fascinating precipitation patterns have been reported. These studies focused on various physicochemical factors [6][7][8][9][10][11][12][13][14][15] including oscillatory growth of hollow microtubes, 12 tube growth with a pinned bubble, 14 and spiral growth of the tube controlled by the application of magnetic force. 15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and self-assembled nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] For the past four centuries, numerous studies of these fascinating precipitation patterns have been reported. These studies focused on various physicochemical factors [6][7][8][9][10][11][12][13][14][15] including oscillatory growth of hollow microtubes, 12 tube growth with a pinned bubble, 14 and spiral growth of the tube controlled by the application of magnetic force. 15 Recently, chemical gardens have received attention as biomimetic materials due to their ability to form a variety of self-assembled structures, [16][17][18][19][20][21][22][23][24][25][26][27] such as silica-rich biomimetic mineral 20 and self-assembled nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigate the precipitation of calcium phosphate. Previously, calcium chloride solution was dropped into sodium phosphate solution yielding a planar chemical garden on the solution top or, under microfluidic conditions, their parallel injection resulted in thin calcium phosphate membranes . Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 , HAP)the most stable form of all calcium phosphate mineralshas gained a lot of interest due to its similarity to the mineral phase of bones , and teeth .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focused our investigation on the generation of a new chemobrionic structure that we called chemobrionic bubbles or jellyfish since they resemble the natural jellyfish. The generation of these chemobrionic jellyfish was based on our recently described CaCl 2 ‐phosphate system [17] …”
Section: Introductionmentioning
confidence: 99%
“…The generation of these chemobrionic jellyfish was based on our recently described CaCl 2 -phosphate system. [17]…”
Section: Introductionmentioning
confidence: 99%